Assessing the impacts of projected climate change on biodiversity in the protected areas of western North America. Issue 5 (29th May 2015) - Langdon, Jesse G. R.; Lawler, Joshua J.
Abstract : Protected areas are a fundamental component of many conservation strategies. They safeguard some of the best examples of unfragmented natural landscapes in many regions, provide important habitat for rare and threatened species, and serve as a refuge from a human‐dominated world. As climates continue to change, species distributions, ecological communities, and ecosystems will be altered. An understanding of the trends in these changes can allow protected area managers to develop more effective climate‐adaptation strategies. Here, we quantify the relative amount of projected potential climate‐driven ecological change across a protected area network by calculating three metrics. We assessed future projected changes in temperature and precipitation, shifts in major vegetation types, and vertebrate species turnover for the protected areas of the Pacific Northwestern region of North America. In general, the degree of projected change in the three metrics followed a longitudinal gradient from the Pacific coast inland toward the continental interior. Protected areas expected to experience the least change are at low elevations near the coast and throughout the Coastal Mountains, whereas areas expected to experience the most change are found at higher elevations in the Rocky Mountains and Great Basin regions. The resulting spatial variation in these impact measures underscores the importance of developing appropriate, location‐specific, climate‐adaptation strategies in response to disparate trends in future environmental change.